FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN MANUFAKTUR - Franjaya, Fandy; Viriany, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to find out the effect of probitability, leverage, firm size, and liquidity on firm value in manufacturing companies that are listed in Indonesia Stock Exchange (IDX) in 2018-2020. This study was conducted on manufacturing companies that are selected using purposive sampling method. This study has total of 162 data, consisting 3 years of data. This study uses Eviews 12 for data processing technique with Fixed Effect model. The result shows that profitability and leverage have significant positive effect on firm value, meanwhile firm size has significant negative effect, and liquidity has no significant effect.